The Concept of Justice in Wage Determination in the Perspective of Maqasid Sharia: Ibn Taimiyyah's Perspective - Alfan Jawahir Muhammad; Hilali Basya; Fina Nurafni (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to describe the concept of justice in wage determination according to Ibn Taimiyyah, viewed through the lens of Maqasid Sharia. This topic is important because in current reality, many institutions fail to pay sufficient attention to the fairness of workers' wages. As a result, wages received are often not proportional to the effort expended nor adequate to meet basic needs. According to Islamic principles, wages should be fair reflecting the worker's contribution and sufficient to cover daily necessities. Ibn Taimiyyah is one of the scholars who emphasizes justice as a core value of Maqasid Sharia and promotes the theory of al-ujrah al-mithliyyah, which bases wage determination on prevailing market rates. This research employs a qualitative, library-based method, using secondary data from various literature sources, and analyzed through descriptive-analytical techniques. The study finds that: (1)Fair wages, according to Ibn Taimiyyah, are those aligned with market standards, combining justice and feasibility; (2)His views are consistent with the objectives of Maqasid Sharia, particularly in realizing justice (tahqiq al-‘adl), protecting life (hifz al-nafs), and promoting equitable wealth distribution (maqasid furu’iyah). These insights offer a valuable perspective on how Islamic teachings can guide ethical labor practices today.